The Modern Group Rotating Savings (Arisan) as Microfinancing Product: Fine Imposement and Islamic Law Respond - Athief, Fauzul Hanif Noor; Sundari, Sundari; Rosyadi, Imron (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 3 (2023): The 6th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2024)
Rotating savings (arisan) has evolved according to current modern society. Arisan nowadays serves as microfinancing using digital platform. However, as as microfinancing unit, it imposes fine and late payment charge as the risk mitigation effort. The purpose of this study is to find out how Islamic law responds towards this phenomena by firstly elaborating the detail of this online arisan mechanism and its fine imposement. This study uses qualitative research to understand phenomena in a social context by interviewing one arisan group and 37 participants. This study found that the fine imposement is applied well within the arisan group and serves as prevention for any late payment from its member. However, the usage of the late payment charge doesn’t follow the guidance made by Indonesia Board of Fatwa (MUI) and the Islamic Economic Laws Compilation (KHES) where such fund must be channeled for social purpose whereas in this case, the owner of the arisan group used the fund for personal purpose only.